Priapism Associated with Lumbar Stenosis in a Dog. Issue 4 (2nd April 2013) - Payan‐Carreira, R; Colaço, B; Rocha, C; Albuquerque, C; Luis, M; Abreu, H; Pires, MA
Contents Priapism, a persistent long‐lasting involuntary erection of the penis, is uncommon in dogs. In this report, the case of a 13‐year‐old male Pointer, referred to our services due to persistent exposition of the penis, is described. This condition was consecutive to an intermittent priapism situation lasting for several days, which has been initially attributed to the inflammation and haematoma associated with a perianal bite. The owners became unable to retract the penis into the prepuce. At presentation, the dog was anorectic for 48 h, intolerant to manipulation, and showed poor body condition and unsteady locomotion. During physical evaluation, a marked engorgement of the local vessels in the prepuce and penis was found. An abdominal X‐ray was asked under the suspicion of a neurogenic origin for the clinical situation, which showed evidences of spondylosis. After discussion of the clinical condition, the owners asked for euthanasia. The necropsy confirmed the engorgement of the regional vessels deriving from the pudendal arteries and blood accumulation within all the cavernous spaces, accompanied by congestion and thrombosis within the erectile structures of the penis. No significant changes were observed in the pelvic organs that could be at the origin of priapism. The lumbar‐sacral spinal regions were carefully inspected and evidenced signs of L7‐S1 stenosis due to spondylosis. The case presented herein is a rare situation of priapism of neurogenic origin in a dog. Necropsy findings suggest that it was consecutive to cauda equina compression due to lumbar spinal stenosis.